Estimating timber depreciation in the Brazilian Amazon - Ronaldo Serôa da Motta; Claudio A. Ferraz do Amaral (Institute for Applied Economic Research (ipea), 2015)
This study applies distinct methodological forest accounting approaches, following Vincent and Hartwick (1997) lines, to estimate economic depreciation of timber exploitation in the Brazilian Amazon region. Although our results may be not definitive ones due to data availability problems, this exercise has proved to bring about issues which, though are theoretical and methodologically fully recognised, are not always revealed in other regional studies. High timber stocks, lack of well defined property rights and informal economic relations are issues related to the Amazonian case that require great deal of caution when one is applying economic depreciation methodologies, as will be addressed on the basis of our results.
Keywords: 330